Association Between Knee Anatomic Metrics and Biomechanics for Male Soldiers Landing With Load. Issue 6 (May 2020) - Kaplan, Jonathan T.; Ramsay, John W.; Cameron, Sarah E.; Seymore, Kayla D.; Brehler, Michael; Thawait, Gaurav K.; Zbijewski, Wojciech B.; Siewerdsen, Jeffrey H.; Brown, Tyler N.
Background: Anterior cruciate ligament (ACL) injury is a military occupational hazard that may be attributed to an individual's knee biomechanics and joint anatomy. This study sought to determine if greater flexion when landing with load resulted in knee biomechanics thought to decrease ACL injury risk and whether knee biomechanics during landing relate to knee anatomic metrics. Hypothesis: Anatomic metrics regarding the slope and concavity of the tibial plateau will exhibit a significant relation to the increased anterior shear force on the knee and decreased knee flexion posture during landing with body-borne load. Study Design: Descriptive laboratory study. Methods: Twenty male military personnel completed a drop landing task with 3 load conditions: light (~6 kg), medium (15% body weight), and heavy (30% body weight). Participants were divided into groups based on knee flexion exhibited when landing with the heavy load (high- and low-Δflexion). Tibial slopes and depth were measured on weightbearing volumetric images of the knee obtained with a prototype cone beam computed tomography system. Knee biomechanics were submitted to a linear mixed model to evaluate the effect of landing group and load, with the anatomic metrics considered covariates. Results: Load increased peak proximal anterior tibial shear force ( P = .034), knee flexion angle ( P = .024), and moment ( P = .001) during landing. Only the high flexion group increased knee flexion ( P < .001) during weighted landings with medium and heavy loads. The low flexion group used greater knee abduction angle ( P = .030) and peak proximal anterior tibial shear force ( P = .034) when landing with load. Anatomic metrics did not differ between groups, but ratio of medial-to-lateral tibial slope and medial tibial depth predicted peak proximal anterior tibial shear force ( P = .009) and knee flexion ( P = .034) during landing, respectively. Conclusion: Increasing knee flexion is an attainable strategy to mitigate risk of ACL injury, but certain individuals may be predisposed to knee forces and biomechanics that load the ACL during weighted landings. Clinical Relevance: The ability to screen individuals for anatomic metrics that predict knee flexion may identify soldiers and athletes who require additional training to mitigate the risk of lower extremity injury.